Pūpūkahi i Holomua: A Story of Hawaiian Education and a Theory of Change - Kukahiko, Kealiʻi; Fernandez, Pono; Sang, Dawn; Yim, Kamuela; Iwane, Anela; Kalama-Macomber, Kaʻanohiokalā; Makua, Kuʻulei; Nakasone, Karen; Tanigawa, Dana; Kim, Kāhea; Cosma Reyes, Leināʻala; Fleming-Nazara, Tristan (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2020)
The Hawaiian kingdom, prior to the illegal overthrow of its monarchy (1893) and the subsequent English-only Law (1896), had boasted a 91-95% literacy rate. Within that learning environment learners had a clear sense of purpose because Hawaiians had a firm grasp of who they were, where they were, and what they had to contribute. Since the English-only Law and US annexation of Hawai‘i (1898), however, the settler colonialschool system has maintained levels of cultural dissonance that have manifested as inequitable student outcomes for Native Hawaiians and Pacific Islanders (NHPI) across multiple academic and disciplinary student indicators (i.e., proficiency, suspension rates, etc). While western law and US compulsory education severed traditional sources of knowledge production that had provided a sustainable model of a‘o (teaching and learning), the ancestors of the Native Hawaiian community were diligent about preserving the keys to their genealogical legacies within more than 120,000 pages of Hawaiian-language newspapers. This collective repository is a resource that helps the Office of Hawaian Education (OHE) rethread Hawaiian education into the tapestry of traditional sources of knowledge production to improve sustainability (cultural, intellectual, environmental, political, etc.) for all learners. OHE uses a theory of change that engages primary and secondary sources, quantitative and qualitative data, in action research that informs Why contemporary circumstances exist, What those contemporary circumstances are, Where we want Hawaiian education to go, and How we are going to get there.